Studies on structural, morphological, optical and antibacterial activity of Pure and Cu-doped MgO nanoparticles synthesized by co-precipitation method. (2018) - Rajendran, V.; Deepa, B.; Mekala, R.
Abstract: Pure and copper (Cu) doped MgO nanoparticles were synthesized by the Sol-gel method. The synthesized nanoparticles retained the cubic phase with periclase structure and it showed small crystalline size for Cu-dopand than the pure confirmed by X-ray diffraction studies. The SEM analysis revealed small berries like morphologies for synthesized NPs. The EDAX studies determined the amount of dopant incorporated into the doped samples. The FTIR provides the functional characteristics of Pure and Cu-doped MgO NPs. From the UV spectra, the band gap was estimated at 4.2888 and 3.8690 eV for Pure and Cu-doped MgO NPs. This band gap reduction might be effectively used in ROS production. In addition, the antibacterial activity of Pure and Cu-doped MgO NPs was carried out against two kinds of bacterial strains: Escherichia coli (G-ve), Staphylococcus aureus (G+ve). The Zone of Inhibition (ZOI) measurement showed better bacterial efficiency in Cu-doped MgO NPs. The shrink in grain size and extending light absorption in far UV region by Cu-doping in MgO NPs contribute equally to the generation of hydrogen peroxide. The H2 O2 penetrate into the cell membranes and kill the bacteria.